The Relationship between Quality of Home Environment and Mental Scores of Children attending the UPM Laboratory Preschool - Abdullah, Rohani; Yaacob, Siti Nur; Baharudin, Rozumah (Universiti Putra Malaysia Press, 1994)
The purpose of this study was to determine the relationship between the quality of home environment that parents provide for their children and the children's mental performance. The study focused on 64 children, aged 5 to 6 years, from the Universiti Pertanian Malaysia Laboratory Preschool. Results of the study show that, generally, most of the children came from a relatively supportive home environment. Consistent with past research, the quality of home environment correlated with family background. Both parents' education and income correlated with the quality of the home environment. The quality of the home environment correlated significantly with the children's mental performance. Children from a cognitively stimulating home environment achieved higher scores on all the subscales of the Weschler Preschool and Primary Scales of Intelligence.